Undrained shear strength of soft clay reinforced with 6mm and 10mm diameter of single bottom ash column - Sharifah Ilya Nur Shuhada , Syed Abdullah (2014)
In today's construction industry, there are various types of ground improvement techniques are need due to existence of problematic soil like soft soil. Stone column is one of the ground improvement techniques to improve the soft soil strength. Bottom ash, as a residue of coal combustion from coal power plants, has similar properties with sand and potentially use as stone columns. The utilization of the industrial by-products is recognized nowadays due to the continuous dwindling of non-renewable natural materials. Furthermore, the large production of bottom ash from coal burning in Malaysia has results in waste issues. So, by using bottom ash column, the disposal problem for bottom ash could extensively be reduced. This research is to show the improvement level in shear strength of soft clay after being reinforced with single bottom ash column. The first study was to determine the physical and mechanical properties of kaolin and bottom ash. The results show that kaolin can be classified as clayey soil and the bottom ash it has relatively similar characteristics to sand. Next, remoulded specimens of 50mm in diameter and 100mm in height of kaolin are tested under Unconfined Compression Test (UCT). A total 35 specimens of kaolin samples were tested using unconfined compression test to determine the shear strength parameter. It can be concluded that the shear strength parameters were affected by the diameter and the height of the column. Diameter for single bottom ash columns are 6 mm, and 10mm. So, the area ratio between the area of the bottom ash column and area of the specimen (Ac/As) are 1.44% and 4.0%.The heights of single bottom ash column are 24mm, 36mm, 48mm4 40mm, 60mm and 80mm. So, the height penetration ratios between the heights of column with the height of the specimen (Hc/Hs) are 0.24, 0.36, 0.48, 0.40, 0.60 and 0.8 respectively. Hence, the volume ratio between the volume of the bottom ash column and volume of the specimen (Vc/Vs) are 0.35%, 0.52%, 0.69% 1.60%, 2.40%, 3.20%. The presence of bottom ash column really improved the shear strength. Nonetheless, column longer than 80% of the soil length, did not lead to further increment in shear strength. This is considered as the "critical column length" where used as vertical granular column.